Description of a new species of Micreriodes Yoshimoto, 1962 (Hymenoptera: Figitidae: Eucoilinae) from the Atlantic Forest in the State of Paraná, Brazil - Chappuis, Edson; Monteiro, Lino B.; Forshage, Mattias; Penteado-Dias, Angélica Maria (Zootaxa, 2026)
A new species of the genus Micreriodes Yoshimoto is described and illustrated in the fauna of the State of Paraná, Brazil: Micreriodes lautus sp. nov. The morphological differences with Micreriodes guamensis are also analyzed. This is the first time any specimen of the genus has ever been identified at the species level outside the Pacific region.